ADAPTASI PERILAKU SAAT DAN PASCA PANDEMI COVID-19 - Wikan Cahya (Jurnal Medika Hutama, 2024)
The COVID-19 pandemic situation is by no means a favorable situation, and tends to cause negative impacts such as feelings of helplessness and hopelessness due to the deterioration of the situation (economically, physically, mentally, etc.). The situation is uncertain and stressful. Communities in the famous Chinatown area of Glodok, where commercial activity is central, have felt this significant negative impact. Government policy interventions had a direct impact on the community's ability to recover. As a result of the government's implementation of extensive social restrictions (PSBB) and restrictions on community movement (PPKM), the Glodok Chinatown community had to adapt to the situation during and after the COVID-19 pandemic. The Glodok Chinatown community must develop resilience to adapt to new environmental conditions. The purpose of this study is to describe the resilience level of Glodok Chinatown during and after the COVID-19 pandemic. The research method used is deductive qualitative descriptive statistical analysis. The research variable is behavioral adaptation (response, adaptation, withdrawal, surrender). The research sample amounted to 89 people using convenience sampling technique. The adaptive level to increase resilience formed in the Glodok Chinatown community is high, medium, and low. The adaptive level is based on the frequency of similar characteristics or adaptability in the application of health protocols and travel mobility. The Glodok Chinatown community tends to have a moderate adaptive level (during the pandemic) and a weak adaptive level (post-pandemic).